2019
DOI: 10.1371/journal.pone.0210862
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous eye movements during focused-attention mindfulness meditation

Abstract: Oculometric measures have been proven to be useful markers of mind-wandering during visual tasks such as reading. However, little is known about ocular activity during mindfulness meditation, a mental practice naturally involving mind-wandering episodes. In order to explore this issue, we extracted closed-eyes ocular movement measurements via a covert technique (EEG recordings) from expert meditators during two repetitions of a 7-minute mindfulness meditation session, focusing on the breath, and two repetition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 107 publications
0
7
0
3
Order By: Relevance
“…Feeling comfortable to keep the eyes closed may however not be the case for people who score higher in neuroticism; indeed, some people prefer to remain in control by keeping their eyes open. Only one study has recently investigated ocular movements relating to mind wandering and meditation, with findings demonstrating higher levels of ocularmetric measures during episodes of mind wandering (Matiz et al 2019). Matiz et al (2019) further suggested that through employing the use of eye-tracking technology during mindfulness meditation, results can provide a more objective insight into mindful mediation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Feeling comfortable to keep the eyes closed may however not be the case for people who score higher in neuroticism; indeed, some people prefer to remain in control by keeping their eyes open. Only one study has recently investigated ocular movements relating to mind wandering and meditation, with findings demonstrating higher levels of ocularmetric measures during episodes of mind wandering (Matiz et al 2019). Matiz et al (2019) further suggested that through employing the use of eye-tracking technology during mindfulness meditation, results can provide a more objective insight into mindful mediation.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study has recently investigated ocular movements relating to mind wandering and meditation, with findings demonstrating higher levels of ocularmetric measures during episodes of mind wandering (Matiz et al 2019). Matiz et al (2019) further suggested that through employing the use of eye-tracking technology during mindfulness meditation, results can provide a more objective insight into mindful mediation. Their research demonstrated that mind-wandering instances are associated with greater levels of ocular activity through comparing eye movements between participants within a focused-breath meditation session or an instructed mind-wandering task.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, остается неясным, существует ли асимметрия между вертикальными саккадами, направленными из нижней части поля зрения в верхнюю (восходящие) и направленными из верхней части поля зрения в нижнюю (нисходящие). В одних исследованиях установлено, что ЛП восходящих саккад ниже по сравнению с нисходящими [17], в других -различия не обнаружены [11,16,18]. В работе А. Matiz et al [18] показано сниже-ние скорости и точности восходящих саккад с возрастом, при этом гипометричные саккады (амплитуда саккады недостаточна для достижения зрительной цели) регистрируются чаще, чем гиперметричные (амплитуда саккад избыточна).…”
unclassified
“…В одних исследованиях установлено, что ЛП восходящих саккад ниже по сравнению с нисходящими [17], в других -различия не обнаружены [11,16,18]. В работе А. Matiz et al [18] показано сниже-ние скорости и точности восходящих саккад с возрастом, при этом гипометричные саккады (амплитуда саккады недостаточна для достижения зрительной цели) регистрируются чаще, чем гиперметричные (амплитуда саккад избыточна). В работе W. Becker, R. Jürgens [19] отмечено, что скорость восходящих саккад с возрастом повышается.…”
unclassified
See 1 more Smart Citation